1982
DOI: 10.1152/jappl.1982.52.5.1257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic conditioning on cardiovascular response to isometric exercise

Abstract: The response to isometric handgrip exercise (IHE) and isometric quadriceps exercise (IQE) (30% maximum voluntary contraction held 3 min) was studied before and after 5 wk of aerobic training. Training exercises involved only the lower extremities. Seventeen healthy unconditioned males aged 21--35 yr were subjects. During training nine subjects received propranolol in doses that provided a high degree of beta-adrenergic blockade; eight received a placebo. All subjects were tested before training or drug and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The higher HR was probably not due to central command since central command affects HR via removal of parasympathetic inhibition (Leonard et al ., 1985; Mitchell et al ., 1989; Seals & Enoka, 1989) rather than increases in sympathetic activity (Seals & Enoka, 1989). The response seen here was more likely due to the latter, since it can be removed with β‐adrenergic receptor blockade (Martin et al ., 1974; Morgan et al ., 1982). A caveat to this is that previous research suggested that central command alone can elicit marked increases in HR and, to a lesser extent, increases in blood pressure and sympathetic nerve activity when associated with near‐maximal effort (Victor et al ., 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher HR was probably not due to central command since central command affects HR via removal of parasympathetic inhibition (Leonard et al ., 1985; Mitchell et al ., 1989; Seals & Enoka, 1989) rather than increases in sympathetic activity (Seals & Enoka, 1989). The response seen here was more likely due to the latter, since it can be removed with β‐adrenergic receptor blockade (Martin et al ., 1974; Morgan et al ., 1982). A caveat to this is that previous research suggested that central command alone can elicit marked increases in HR and, to a lesser extent, increases in blood pressure and sympathetic nerve activity when associated with near‐maximal effort (Victor et al ., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the increase in MAP was relatively larger than the increase in HR. Central command‐dependent increases in HR likely accounted for the rise in blood pressure seen in the first few minutes of isometric exercise in both ARM and LEG (Martin et al ., 1974; Morgan et al ., 1982; Maciel et al ., 1987). After 2–3 min of exercise, the effects of the muscle chemoreflex likely played a more critical role in determining the pressor responses to isometric exercise.…”
Section: Discussionmentioning
confidence: 99%
“…10,33 However, it has been shown that aerobic training may attenuate the hemodynamic responses seen from static exertion. Morgan and associates 135 have studied the effect of aerobic conditioning on cardiovascular response to static exercise. They have shown that running will decrease heart rate and blood pressure response to static exercise (40% leg extension), but no changes were observed in response to static handgrip.…”
Section: Cardiovascular Responses To Static and Dynamic Resistance Trmentioning
confidence: 99%